Heartwood Extract of Pterocarpus marsupium Roxb. Offers Defense against Oxyradicals and Improves Glucose Uptake in HepG2 Cells - Mohammad Irfan Dar; Sahar Rafat; Kapil Dev; Sageer Abass; Mohammad Umar Khan; Walaa A. Abualsunun; Samar S. Murshid; Sayeed Ahmad; Mohammad Irfan Qureshi (Metabolites, 2022)
Diabetes mellitus leads to cellular damage and causes apoptosis by oxidative stress. Heartwood extract of Pterocarpus marsupium has been used in Ayurveda to treat various diseases such as leprosy, diabetes, asthma, and bronchitis. In this study, we worked out the mechanism of the antidiabetic potential of methanolic heartwood extract of Pterocarpus marsupium (MPME). First, metabolic profiling of MPME was done using gas chromatography-mass spectrometry (GCMS), ultra-performance liquid chromatography-mass spectroscopy (UPLC-MS), and high-performance thin-layer chromatography (HPTLC) to identify phenols, flavonoids, and terpenoids in MPME. Biological studies were carried out in vitro using the HepG2 cell line. Many antidiabetic compounds were identified including Quercetin. Methanolic extract of MPME (23.43 µg/mL–93.75 µg/mL) was found to be safe and effective in reducing oxyradicals in HepG2 cells. A concentration of 93.75 µg/mL improved glucose uptake efficiently. A significant decrease in oxidative stress, cell damage, and apoptosis was found in MPME-treated HepG2 cells. The study suggests that the heartwood of Pterocarpus marsupium offers good defense in HepG2 cells against oxidative stress and improves glucose uptake. The results show the significant antidiabetic potential of MPME using a HepG2 cell model. The effect seems to occur by reducing oxidative stress and sensitizing the cells towards glucose uptake, hence lowering systemic glucose levels, as well as rescuing ROS generation.